Pendekatan Sastra Dalam Kisah-Kisah Al-Qur’an Perspektif Muḥammad Aḥmad Khalafullāh - Sofwan, Nurkholis (Al Ashriyyah, 2021)
This paper examines the literary approach used by Khalafullāh to interpret the stories in the Qur'an. Most of the scholars state that the stories in the Qur’an are real and true, but some other scholars state that the stories in the Qur'an are only parables, and that historical evidence is not necessary to prove the truth of the story. In this respect, Khalafullāh is more inclined towards the second opinion. He considered that the Qur'an was a book full of literary, so he used a literary approach in interpreting the stories in the Qur'an. This paper seeks to explain the literary approach that Khalafullāh offered to interpret the stories in the Qur'an. then compare it with the views of the classical commentators on the stories in the Qur'an with their respective approaches. This paper concludes that a literary approach is offered Khalafullāh is able to reveal the psychological side of the stories in the Qur'an, so that the message in the story is in accordance with the purpose of being transmitted. In addition, he also explicitly stated that Muslims do not see the stories in the Qur'an as mere historical texts, but rather understand them as texts that contain religious, moral and social norms guidance.